Charge Redistribution and Transport in Molecular Contacts - Corso, Martina; Ondráček, Martin; Lotze, Christian; Hapala, Prokop; Franke, Katharina J; Jelínek, Pavel; Pascual, J Ignacio (Physical review letters, 2015)
The forces between two single molecules brought into contact, and their connection with charge transport through the molecular junction, are studied here using non contact AFM, STM, and density functional theory simulations. A carbon monoxide molecule approaching an acetylene molecule (C_{2}H_{2}) initially feels weak attractive electrostatic forces, partly arising from charge reorganization in the presence of molecular . We find that the molecular contact is chemically passive, and protects the electron tunneling barrier from collapsing, even in the limit of repulsive forces. However, we find subtle conductance and force variations at different contacting sites along the C_{2}H_{2} molecule attributed to a weak overlap of their respective frontier orbitals.